Ectopic Expression of Poplar PsnCYCD1;1 Reduces Cell Size and Regulates Flower Organ Development in Nicotiana tabacum - Zhao, Zhongnan; Zheng, Tangchun; Dai, Lijuan; Liu, Yi; Li, Shuang; Qu, Guanzheng (Frontiers in Plant Science, 2022)
D-type cyclin (CYCD) gene, as the rate limiting enzyme in G1 phase of cell cycle, plays a vital role in the process of plant growth and development. Early studies on plant cyclin mostly focused on herbs such as Arabidopsis thaliana. The sustainable growth ability of woody plants is a unique characteristic in the study of plant cyclin. Here, the promoter of PsnCYCD1;1 was cloned from poplar by PCR and genetically transformed into tobacco. A strong GUS activity was observed in the areas with vigorous cell division such as stem tip, lateral bud and young leaf. The PsnCYCD1;1-GFP fusion expression vector was transformed into tobacco, and the green fluorescence signal was observed in the nucleus. Compared with the control plant, the transgenic tobacco showed significant changes in the flower organs, such as enlargement of sepals, petals and fruits. Furthermore, the stems of transgenic plants were slightly curved at each stem node, the leaves were curled on adaxial side, and the fruits were seriously aborted after artificial pollination. Microscopic observation showed that the epidermal cells of petals, leaves and seed coat of transgenic plants became smaller. The transcriptional levels of endogenous genes, such as NtCYCDs, NtSTM, NtKNAT1 and NtASs, were upregulated by PsnCYCD1;1. Therefore, PsnCYCD1;1 gene played an important role in the regulation of flower organ and stem development, providing new understanding for the functional characterization of CYCD gene and new resources for improving the ornamental value of horticultural plants.